Avaliação de estruturas veiculares soldadas submetidas à carregamentos cíclicos: critérios de inspeção e aceitabilidade - Costa, Admilson Vieira da (1998)
In this work it has been was performed a study on the influence of welding defects such as incomplete joint penetration, undercut and excessive reinforcement, on the fatigue resistance of welded joints typical in vehicular alterations. With this study it is aimed to show that acceptance and welds inspection criteria performed in vehicular structures must be standardized. The experimental procedure has been based in the generation of such defects, in several leveis, in butt welded test plates 9,5 mm thick. Samples were taken from these test plate and cyclic loading was applied perpendicular to the weld bead. Those samples were tested under fatigue up to fracture, in a complete reverse stress cycle. The results show that incomplete joint penetration defects of about 1 mm cause a reduction of approximately 36% in the fatigue endurance of the welded joint. For the undercut defects up to 1,6 mm, the reduction was approximately 10%. Defects of excessive reinforcement were not so harmful, except when associated with other kinds of defects such as overlap or lack of fusion. The results show that there is a criticai size in such a way that an acceptance criterion could be experimentally established.